2015
DOI: 10.1111/his.12808
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of NSCLC tumour heterogeneity, proliferative and 18F‐FDG PET indices reveals Ki67 prognostic role in adenocarcinomas

Abstract: Aims: The role of tumour metabolic and proliferative indices in predicting non-small-cell lung cancer (NSCLC) patients' prognosis is unclear. We correlated fluorine 18 ( 18 F)-fluorodeoxyglucose (FDG)-positron emission tomography (PET) value and Ki67 index to patients' survival, taking into account tumour heterogeneity, disease characteristics and genetic aberrations. Methods and results: A series of 383 NSCLCs was arranged into tissue microarrays and Ki67 staining was analysed by immunohistochemistry. The max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…In addition, Ki67 is also used as a prognostic and diagnostic index for the evaluation of cancer biopsies, including lung cancer [11, 12]. Our results confirmed that Ki67 was an independent prognostic factor in NSCLC (Table 2).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, Ki67 is also used as a prognostic and diagnostic index for the evaluation of cancer biopsies, including lung cancer [11, 12]. Our results confirmed that Ki67 was an independent prognostic factor in NSCLC (Table 2).…”
Section: Discussionsupporting
confidence: 80%
“…Prior studies of human NSCLC have identified intratumoral heterogeneity in terms of proliferative activity [30], cellular histology [31], anaplastic lymphoma kinase rearrangements [32], and PD-L1 expression [9]. Thus, heterogeneity of CD8 + T cell infiltrations is expected.…”
Section: Discussionmentioning
confidence: 99%
“…It is present in all active phases of the cell cycle, but absent from resting cells, thus, indicating the proliferating cell fraction (39). Ki-67 is a prognostic biomarker in several tumor entities, for example, breast cancer, lymphoma, neuroendocrine neoplasia and NSCLC (40)(41)(42)(43)(44)(45). The Ki-67 index could also be employed to investigate the association between Testin expression and NSCLC cell proliferation.…”
Section: Discussionmentioning
confidence: 99%